Fe-Ni / biomass charcoal catalyst and preparation method and application thereof

By preparing Fe-Ni/biomass carbon catalyst, using pickling, oxidation modification and ultrasonic impregnation technologies, the problem of difficult tar removal during biomass pyrolysis gasification is solved, and the efficient and low-cost tar cracking effect is achieved.

CN119733517APending Publication Date: 2025-04-01NORTH CHINA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411940655.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The tar produced during the pyrolysis and gasification of biomass is difficult to remove efficiently. The existing catalysts are expensive and have low catalytic activity, making it difficult to meet industrial needs.

Method used

The Fe-Ni/biomass carbon catalyst is used to increase the oxygen-containing functional group content of biomass carbon through pickling and oxidation modification treatment, and the iron salt and nickel salt are introduced in combination with ultrasonic impregnation technology to form a catalyst with high specific surface area and high dispersion active components.

Benefits of technology

It has achieved efficient catalytic cracking of tar at lower reaction temperatures (such as 550°C), which has improved the catalytic capacity of biomass carbon, reduced the production cost of catalysts, and expanded its application potential in tar catalysis.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of biomass solid waste utilization, and discloses a Fe-Ni / biomass charcoal catalyst and a preparation method and application thereof. The preparation method comprises the following steps: pickling a biomass raw material, modifying with hydrogen peroxide, and dipping in an aqueous solution of ferric salt and nickel salt to obtain a precursor; and calcining the precursor in a protective atmosphere to obtain the Fe-Ni / biomass charcoal catalyst. According to the catalyst disclosed by the invention, the waste biomass is efficiently combined with the iron-nickel active components, so that the tar catalysis capability of the biomass charcoal at medium and low temperatures is improved, the problem that a single active component is easy to inactivate in a catalysis process is solved, and the application potential of the biomass charcoal in tar catalysis is expanded. The catalyst is good in catalytic performance and high in stability, and the conversion rate of catalyzing methylbenzene at the low reaction temperature of 550 DEG C can reach 90% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomass solid waste utilization, and in particular to a Fe-Ni / biomass carbon catalyst and a preparation method and application thereof. Background Art

[0002] Biomass pyrolysis and gasification is a thermochemical conversion technology that efficiently converts the chemical energy contained in biomass into fuel gas. It has the characteristics of high efficiency and cleanliness, and is considered to be an effective way to solve the current energy crisis. However, the biomass pyrolysis and gasification process will produce a large amount of tar, which will not only block the pipeline and affect the normal use of the equipment, but also pollute the environment and threaten human safety. Therefore, the efficient removal of tar is an urgent problem that the biomass pyrolysis and gasification industry needs to solve.

[0003] At present, the main methods for removing tar include physical purification, thermal cracking and catalytic cracking. The physical purification method only transfers or concentrates the tar, and the process is complicated; the thermal cracking method generally has a reaction temperature above 1100℃ and has high requirements for equipment; while the catalytic cracking method has attracted much attention due to its wide range of applicable conditions and high economic efficiency.

[0004] Commonly used cracking catalysts mainly include natural minerals, alkali metals and transition metal catalysts. Although natural minerals such as dolomite play a good catalytic role in biomass pyrolysis and gasification, the catalytic activity is generally low; alkali metal and transition metal catalysts are expensive, and research mainly focuses on the development of a single active component, with poor results. Based on this, how to prepare a low-cost composite catalyst with multiple active components is of great significance to the biomass pyrolysis and gasification industry. Summary of the invention

[0005] The purpose of the present invention is to provide a Fe-Ni / biomass charcoal catalyst and a preparation method and application thereof, so as to solve the above-mentioned problems existing in the prior art.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a Fe-Ni / biomass charcoal catalyst, comprising the following steps:

[0008] The biomass raw material is acid-washed, and then modified with a hydrogen peroxide solution to obtain a modified biomass raw material;

[0009] The modified biomass raw material, iron salt, nickel salt and water are mixed, and the modified biomass raw material is immersed in the aqueous solution of iron salt and nickel salt to obtain a precursor;

[0010] The precursor is calcined under a protective atmosphere to obtain a Fe-Ni / biomass carbon catalyst.

[0011] Preferably, in the above-mentioned method for preparing a Fe-Ni / biomass charcoal catalyst, the biomass raw material includes one or more of trees, wheat straw, corn stalks, bagasse, and waste paper.

[0012] Preferably, in the above-mentioned method for preparing a Fe-Ni / biochar catalyst, the acid used for pickling is a sulfuric acid solution; the mass concentration of the sulfuric acid solution is 0.5-2.5%; the temperature of the pickling is 120-140°C; and the time of the pickling is 2-4h.

[0013] Preferably, in the above-mentioned method for preparing a Fe-Ni / biomass charcoal catalyst, the mass concentration of the hydrogen peroxide solution is 15-20%.

[0014] Preferably, in the above-mentioned method for preparing a Fe-Ni / biomass charcoal catalyst, the modification temperature is 50-60° C.; and the modification time is 0.5-1 h.

[0015] Preferably, in the above-mentioned method for preparing the Fe-Ni / biomass carbon catalyst, the usage ratio of the modified biomass raw material, iron salt, nickel salt and water is 10-20 g: 0.01-1 mol: 0.01-1 mol: 200 mL.

[0016] Preferably, in the above-mentioned method for preparing a Fe-Ni / biomass charcoal catalyst, the impregnation time is 0.5 to 1 h; the impregnation process also includes ultrasound; and the power of the ultrasound is 500W.

[0017] Preferably, in the above-mentioned method for preparing a Fe-Ni / biochar catalyst, the calcination temperature is 650-750° C.; and the calcination time is 1-2 h.

[0018] The present invention also provides a Fe-Ni / biomass charcoal catalyst prepared by a method for preparing the Fe-Ni / biomass charcoal catalyst.

[0019] The present invention also provides an application of a Fe-Ni / biomass carbon catalyst in catalytic cracking of tar.

[0020] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The present invention uses biomass with a high content of oxygen-containing functional groups after acid washing and oxidation as a carbon-based carrier, introduces iron salt and nickel salt as an activator and metal-bearing material through ultrasonic impregnation, and calcines under an inert atmosphere to obtain a Fe-Ni / biomass charcoal tar cracking catalyst with a high specific surface area and highly dispersed active components. The biomass raw materials in the catalyst of the present invention are widely sourced, and the tar cracking catalyst is prepared using various types of wood cellulose such as trees, wheat straw, corn stalks, bagasse, and waste paper as carbon carriers, making full use of biomass waste and achieving the purpose of treating waste with waste. The catalyst prepared by the present invention uses waste biomass and iron-nickel active components to efficiently combine, improve the catalytic ability of biomass charcoal for tar at medium and low temperatures, improve the problem of easy deactivation of a single active component during the catalytic process, and expand the application potential of biomass charcoal in tar catalysis. The catalyst has good catalytic performance, and the conversion rate of catalytic toluene can reach more than 90% at a relatively low reaction temperature of 550°C.

[0022] (2) The catalyst preparation method of the present invention is simple and low-cost, which is conducive to large-scale industrial application. DETAILED DESCRIPTION

[0023] The present invention provides a method for preparing a Fe-Ni / biomass charcoal catalyst, comprising the following steps:

[0024] The biomass raw material is acid-washed, and then modified with a hydrogen peroxide solution to obtain a modified biomass raw material;

[0025] The modified biomass raw material, iron salt, nickel salt and water are mixed, and the modified biomass raw material is immersed in the aqueous solution of the iron salt and the nickel salt to obtain a precursor;

[0026] The precursor is calcined under a protective atmosphere to obtain a Fe-Ni / biomass carbon catalyst.

[0027] In the present invention, the biomass raw material is further dried and crushed before use; the drying is preferably carried out in an oven at 60° C. for 24 hours; and the particle size after crushing is preferably 50 to 100 meshes.

[0028] In the present invention, the biomass raw material preferably includes one or more of trees, wheat straw, corn stalks, bagasse, and waste paper, more preferably one or more of wheat straw, corn stalks, and bagasse, and more preferably corn stalks.

[0029] In the present invention, the acid used for pickling is preferably a sulfuric acid solution; the mass concentration of the sulfuric acid solution is preferably 0.5-2.5%, more preferably 1-2.5%, more preferably 2.5%; the temperature of the pickling is preferably 120-140°C, more preferably 120-135°C, more preferably 120°C; the time of the pickling is preferably 2-4h, more preferably 2-3h, more preferably 2h.

[0030] In the present invention, the pickling process also includes stirring; the present invention does not limit the stirring speed, and the conventional stirring speed in the art can be used.

[0031] In the present invention, the acid wash further includes washing and vacuum drying; the washing is preferably water washing to neutrality; the vacuum drying is preferably vacuum drying in a vacuum oven at 60° C. for 24 hours.

[0032] In the present invention, the mass concentration of the hydrogen peroxide solution is preferably 15-20%, more preferably 15-17%, and more preferably 15%.

[0033] In the present invention, the modification temperature is preferably 50-60°C, more preferably 55-60°C, and more preferably 60°C; the modification time is preferably 0.5-1h, more preferably 0.6-1h, and more preferably 1h.

[0034] In the present invention, the modification process also includes stirring; the present invention does not limit the stirring speed, and the conventional stirring speed in the art can be used.

[0035] In the present invention, the modification further includes washing and drying; the washing is preferably washing with water until neutral; the drying is preferably drying in an oven at 60° C. for 24 hours.

[0036] The present invention improves the content of oxygen-containing functional groups in biochar through acid washing and oxidation modification treatment. The oxygen functional groups are active sites for heterogeneous reforming of tar molecules. The oxygen-containing groups can form some acidic centers to combine with polyaromatic rings to activate the reaction activity.

[0037] In the present invention, the iron salt is preferably ferric nitrate nonahydrate; and the nickel salt is preferably nickel nitrate hexahydrate.

[0038] In the present invention, the usage ratio of the modified biomass raw material, iron salt, nickel salt and water is preferably 10-20 g: 0.01-1 mol: 0.01-1 mol: 200 mL, more preferably 10-15 g: 0.05-0.61 mol: 0.04-0.3 mol: 200 mL, and more preferably 10 g: 0.1 mol: 0.1 mol: 200 mL.

[0039] In the present invention, the impregnation time is preferably 0.5 to 1 h, more preferably 0.5 to 0.8 h, and more preferably 0.5 h; the impregnation process also includes ultrasound; the power of the ultrasound is preferably 500 W. Based on the principles of ultrasonic cavitation effect and thermal effect, the present invention adopts ultrasonic impregnation method to improve the dispersibility of active components, increase active sites, and enhance catalytic performance.

[0040] In the present invention, the impregnation further includes standing and vacuum drying; the standing time is preferably 12 hours; and the vacuum drying is preferably vacuum drying in a vacuum oven at 60° C. for 24 hours.

[0041] In the present invention, the calcination temperature is preferably 650-750°C, more preferably 680-720°C, and more preferably 700°C; the calcination time is preferably 1-2h, more preferably 1-1.5h, and more preferably 1h.

[0042] In the present invention, the protective atmosphere is preferably nitrogen.

[0043] The present invention also provides a Fe-Ni / biomass charcoal catalyst prepared by a method for preparing the Fe-Ni / biomass charcoal catalyst.

[0044] The present invention also provides an application of a Fe-Ni / biomass carbon catalyst in catalytic cracking of tar.

[0045] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] Example 1

[0047] This embodiment provides a Fe-Ni / biomass carbon catalyst, and the preparation method thereof comprises the following steps:

[0048] (1) Dry the corn stalks in an oven at 60°C for 24 hours, then crush them with a crusher, and select 50-100 mesh corn stalk powder after screening for use; add an appropriate amount of corn stalk powder to a 2.5% sulfuric acid solution, heat and stir in an oil bath for pickling, wherein the heating temperature is 120°C and the stirring time is 2 hours; after the pickling is completed, wash with deionized water for multiple times until the filtrate is neutral and no SO4 is detected 2-ions; then the filtered solid was placed in a vacuum oven and dried at 60°C for 24 hours to obtain acid-washed corn stalks; 100 mL of a 15% hydrogen peroxide solution was prepared, a certain amount of acid-washed corn stalks was added, heated and stirred at 60°C for 1 hour, and then filtered, washed, and dried at 60°C for 24 hours to obtain modified corn stalks;

[0049] (2) Weigh 0.1 mol of Fe(NO3)3·9H2O solid and 0.1 mol of Ni(NO3)2·6H2O solid respectively, dissolve in 200 mL of deionized water to obtain a mixed solution of iron and nickel, add 10 g of modified corn stalks to the solution, place in an ultrasonic generator for ultrasonic immersion, so that the active components of iron and nickel are accelerated to enter the gaps of the modified corn stalks and are evenly distributed, wherein the ultrasonic power is 500 W and the ultrasonic time is 0.5 h; after the ultrasonic treatment, let it stand for 12 h, then place in a vacuum oven at 60°C and dry for 24 h, and grind to obtain a precursor;

[0050] (3) 400 mL / min of N2 was introduced into the horizontal tubular reactor until the air in the reactor was completely expelled, and then the N2 flow rate was adjusted to 200 mL / min. Under this condition, the reactor was heated to 700°C at a rate of 10°C / min, and then 5 g of the precursor was added. The mixture was calcined for 1 h in a N2 atmosphere and cooled to obtain the Fe-Ni / biochar catalyst.

[0051] The Fe-Ni / biomass charcoal catalyst prepared as above was used for toluene removal experiment. First, 1g of Fe-Ni / biomass charcoal catalyst was placed in a fixed bed reactor, and nitrogen was introduced to remove the air in the reactor. Then, the fixed bed reactor was heated. When the temperature rose to 550°C, toluene and deionized water (water-to-carbon ratio = 3) were fed into the reactor with nitrogen as carrier gas. The toluene feed amount was 0.2mL / min. The reaction gas was collected and analyzed, and it was found that the conversion rate of toluene by the Fe-Ni / biomass charcoal catalyst reached 92%.

[0052] Example 2

[0053] This embodiment provides a Fe-Ni / biomass carbon catalyst, and the preparation method thereof comprises the following steps:

[0054] (1) Dry the corn stalks in an oven at 60°C for 24 hours, then crush them with a crusher, and select 50-100 mesh corn stalk powder after screening for use; add an appropriate amount of corn stalk powder to a 1.5% sulfuric acid solution, heat and stir in an oil bath for pickling, wherein the heating temperature is 130°C and the stirring time is 2 hours; after the pickling is completed, wash with deionized water for multiple times until the filtrate is neutral and no SO4 is detected 2-ions; then the filtered solid was placed in a vacuum oven and dried at 60°C for 24 hours to obtain acid-washed corn stalks; 100 mL of a 15% hydrogen peroxide solution was prepared, a certain amount of acid-washed corn stalks was added, heated and stirred at 60°C for 1 hour, and then filtered, washed, and dried at 60°C for 24 hours to obtain modified corn stalks;

[0055] (2) Weigh 0.1 mol of Fe(NO3)3·9H2O solid and 0.05 mol of Ni(NO3)2·6H2O solid respectively, dissolve in 200 mL of deionized water to obtain a mixed solution of iron and nickel, add 10 g of modified corn stalks to the solution, place in an ultrasonic generator for ultrasonic impregnation, so that the active components of iron and nickel are accelerated to enter the gaps of the modified corn stalks and are evenly distributed, wherein the ultrasonic power is 500 W and the ultrasonic time is 0.5 h; after the ultrasonic treatment, let it stand for 12 h, then place in a vacuum oven at 60°C and dry for 24 h, and grind to obtain a precursor;

[0056] (3) 400 mL / min of N2 was introduced into the horizontal tubular reactor until the air in the reactor was completely expelled, and then the N2 flow rate was adjusted to 200 mL / min. Under this condition, the temperature was increased at 10°C / min to heat the reactor to 700°C, and then 5 g of the precursor was added, calcined for 1 h in a N2 atmosphere, and the Fe-Ni / biochar catalyst was obtained after cooling.

[0057] The Fe-Ni / biomass charcoal catalyst prepared as above was used for toluene removal experiment. First, 1g of Fe-Ni / biomass charcoal catalyst was placed in a fixed bed reactor, and nitrogen was introduced to remove the air in the reactor. Then, the fixed bed reactor was heated. When the temperature rose to 550°C, toluene and deionized water (water-to-carbon ratio = 3) were fed into the reactor with nitrogen as carrier gas. The toluene feed amount was 0.2mL / min. The reaction gas was collected and analyzed, and it was found that the conversion rate of toluene by the Fe-Ni / biomass charcoal catalyst reached 90%.

[0058] Example 3

[0059] This embodiment provides a Fe-Ni / biomass carbon catalyst, and the preparation method thereof comprises the following steps:

[0060] (1) Dry the wheat straw in an oven at 60°C for 24 hours, then crush it with a crusher, and select 50-100 mesh wheat straw powder after screening for use; add an appropriate amount of corn stalk powder to a 2.5% sulfuric acid solution, heat and stir in an oil bath for acid washing, wherein the heating temperature is 120°C and the stirring time is 2 hours; after the acid washing, wash it with deionized water for multiple times until the filtrate is neutral and no SO4 is detected 2-ions; then the filtered solid was placed in a vacuum oven and dried at 60°C for 24 hours to obtain acid-washed wheat straw; 100 mL of a 15% hydrogen peroxide solution was prepared, a certain amount of acid-washed wheat straw was added, heated and stirred at 60°C for 1 hour, and then filtered, washed, and dried at 60°C for 24 hours to obtain modified wheat straw;

[0061] (2) Weigh 0.1 mol of Fe(NO3)3·9H2O solid and 0.05 mol of Ni(NO3)2·6H2O solid respectively, dissolve in 200 mL of deionized water to obtain a mixed solution of iron and nickel, add 10 g of modified wheat straw, place in an ultrasonic generator for ultrasonic impregnation, so that the active components of iron and nickel are accelerated to enter the gaps of the modified wheat straw and are evenly distributed, wherein the ultrasonic power is 500 W and the ultrasonic time is 0.5 h; after the ultrasonic treatment, let it stand for 12 h, then place in a vacuum oven at 60°C and dry for 24 h, and grind to obtain a precursor;

[0062] (3) 400 mL / min of N2 was introduced into the horizontal tubular reactor until the air in the reactor was completely expelled, and then the N2 flow rate was adjusted to 200 mL / min. Under this condition, the temperature was increased at 10°C / min to heat the reactor to 700°C, and then 5 g of the precursor was added, calcined for 1 h in a N2 atmosphere, and the Fe-Ni / biochar catalyst was obtained after cooling.

[0063] The Fe-Ni / biomass charcoal catalyst prepared as above was used for toluene removal experiment. First, 1g of Fe-Ni / biomass charcoal catalyst was placed in a fixed bed reactor, and nitrogen was introduced to remove the air in the reactor. Then, the fixed bed reactor was heated. When the temperature rose to 550°C, toluene and deionized water (water-to-carbon ratio = 3) were fed into the reactor with nitrogen as carrier gas. The toluene feed amount was 0.2mL / min. The reaction gas was collected and analyzed, and it was found that the conversion rate of toluene by the Fe-Ni / biomass charcoal catalyst reached 91%.

[0064] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a Fe-Ni / biomass carbon catalyst, characterized in that: The following steps are involved: The biomass raw material is acid-washed, and then modified with a hydrogen peroxide solution to obtain a modified biomass raw material; The modified biomass raw material, iron salt, nickel salt and water are mixed, and the modified biomass raw material is immersed in the aqueous solution of the iron salt and the nickel salt to obtain a precursor; The precursor is calcined under a protective atmosphere to obtain a Fe-Ni / biomass carbon catalyst.

2. The method for preparing a Fe-Ni / biomass carbon catalyst according to claim 1, characterized in that: The biomass raw materials include one or more of trees, wheat straw, corn stalks, bagasse, and waste paper.

3. The method for preparing a Fe-Ni / biomass carbon catalyst according to claim 2, characterized in that: The acid used for pickling is a sulfuric acid solution; the mass concentration of the sulfuric acid solution is 0.5-2.5%; the temperature of the pickling is 120-140° C.; and the time of the pickling is 2-4 hours.

4. The method for preparing a Fe-Ni / biomass carbon catalyst according to claim 1 or 3, characterized in that: The mass concentration of the hydrogen peroxide solution is 15-20%.

5. The method for preparing a Fe-Ni / biomass carbon catalyst according to claim 4, characterized in that: The modification temperature is 50-60° C.; the modification time is 0.5-1 h.

6. The method for preparing a Fe-Ni / biomass carbon catalyst according to claim 5, characterized in that: The usage ratio of the modified biomass raw material, iron salt, nickel salt and water is 10-20 g: 0.01-1 mol: 0.01-1 mol: 200 mL.

7. The method for preparing a Fe-Ni / biomass carbon catalyst according to claim 3 or 6, characterized in that: The immersion time is 0.5 to 1 hour; the immersion process also includes ultrasound; the power of the ultrasound is 500W.

8. The method for preparing a Fe-Ni / biochar catalyst according to claim 7, characterized in that: The calcination temperature is 650-750° C. and the calcination time is 1-2 hours.

9. An Fe-Ni / biomass carbon catalyst obtained by the preparation method of an Fe-Ni / biomass carbon catalyst as described in any one of claims 1 to 8.

10. Use of the Fe-Ni / biochar catalyst according to claim 9 in catalytic cracking of tar.